The Role of Waste Bank Digital in Circular Economy Value-Added Creation - Sinaga, Amaliah Rosita (LPPM Universitas Bina Bangsa, 2024)
Waste that is not processed economically and effectively will damage the life of the surrounding environment. One way that the community can reduce the amount of waste entering the environment is by creating a waste bank. Bank Sampah Digital is a social enterprise committed to community waste management. This research aims to find out the role of waste banks in creating added value in the circular economy. The research method used is qualitative research with interview and triangulation methods. The result of this research is that the Bank Sampah Digital creates added value in the circular economy, especially from the sorting of waste that has been done by the community and weighed by the waste bank. This form of economic added value is in the form of financial savings or rupiah. These savings can be used for business capital expenditures, education, and others that can help the community's economy.